Australian chiropractors’ perception of the clinical relevance of anatomical sciences and adequacy of teaching in chiropractic curricula - Giuriato, Rosemary (Chiropr Man Therap, 2020)
BACKGROUND: Human anatomy education is compulsory in the undergraduate curriculum in all Australian chiropractic education programs. There is very little data on clinicians’ perceptions of the adequacy of their anatomy training and its relevance to practice. The aims of this study were to evaluate Australian registered chiropractors’ perceptions on the relevance and adequacy of anatomy training for clinical practice and analyse their opinion on the usefulness of the teaching resources utilized during their preprofessional training. METHODS: A questionnaire-based survey was conducted on a sample of Australian registered chiropractors focussing on the adequacy of their anatomical science (gross anatomy, histology, neuroanatomy and embryology) training and the clinical relevance of each individual sub-discipline, and the perceived value of each of the different anatomy teaching resources utilized. RESULTS: A total of 128 completed surveys were returned from an estimated 387 attendees at two national chiropractic conferences (estimated 33% response rate). The respondents represent 2.6% of registered chiropractors in Australia in 2016 and were representative in terms of gender (66.4% male) but not age, with older generations being over-represented (peak age group 35–44 vs. 25–34). The majority of the survey respondents obtained their chiropractic qualification in Australia (89.1%) and graduated after 1990 with an average of 21.7 years (SD = 11.3, range = 1–44) in practice. Respondents were equally likely to have undertaken anatomy training in Medicine, Science, Health Science, or other faculties. The disciplines perceived most relevant for clinical practice were neuroanatomy (100% of respondents agreeing) and gross anatomy (99.2%), followed by histology (86.0%) and embryology (81.1%). Respondents also perceived their training to be most adequate in neuroanatomy (99.3%) and gross anatomy (99.2%) followed by histology (91.4%) and embryology (85%). Respondents confirmed exposure to a varied suite of anatomy teaching tools utilized during their pre-professional training and highly valued access to cadavers and prosected specimens. CONCLUSIONS: The majority of respondents perceived anatomy as highly relevant to their clinical practice and noted that it was adequately taught within a wide range of educational approaches. These results will assist educators to refine content and delivery of anatomy course offerings to maximize relevance in chiropractic clinical practice.